2020
DOI: 10.14237/ebl.11.1.2020.1686
|View full text |Cite
|
Sign up to set email alerts
|

Ethnoichthyology of Fishing Communities in the Lower Valley of Ouémé in Benin, West Africa

Abstract: Ethno-ichthyological knowledge can improve fisheries management. This study covers interactions between ecological, morphological, and sociocultural aspects pertaining to the fish of the Tovè River, which is located in the largest fishing area in the Republic of Benin (Ouémé Valley), West Africa. In particular, data were collected on fishing methods and techniques, fishing equipment, and ichthyofauna by noting vernacular names followed by identification traits, taste and dietary value, medicinal use, and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The quick growth and good nutritional content of this great food fish prompted research into its aquaculture potential [ 51 ]. Catfish, for example, is a popular food in the fishing community, indicating a complex interaction of symbolic and cultural aspects, as well as materialistic or practical factors, such as the region's availability of this resource [ 52 ]. Hasan, Ahmad [ 53 ] reported that some fishes from the river Swat, Pakistan, such as Racoma labiata , Schizothorax plagiostomus , Mastacembelus armatus , Tor macrolepis , Cyprinus carpio and trout species are consumed as food hence deemed more economically important.…”
Section: Discussionmentioning
confidence: 99%
“…The quick growth and good nutritional content of this great food fish prompted research into its aquaculture potential [ 51 ]. Catfish, for example, is a popular food in the fishing community, indicating a complex interaction of symbolic and cultural aspects, as well as materialistic or practical factors, such as the region's availability of this resource [ 52 ]. Hasan, Ahmad [ 53 ] reported that some fishes from the river Swat, Pakistan, such as Racoma labiata , Schizothorax plagiostomus , Mastacembelus armatus , Tor macrolepis , Cyprinus carpio and trout species are consumed as food hence deemed more economically important.…”
Section: Discussionmentioning
confidence: 99%
“…We collect and analyze the qualitative and quantitative data with descriptive statistical analysis. This methodology is summarized and adopted from Djidohokpin et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…These remarks show the importance of studying the classificatory value of local names of fish in each tribe. Similarly, Djidohokpin et al [21] did not explain the etymology of the names or their theoretical basis.…”
Section: Traditional Nomenclature Of Local Names Of Fish Speciesmentioning
confidence: 98%
“…In Benin, Djidohokpin et al [21] interviewed fishermen in Tovè locality on ethnoichthyological issues of fishes in the Tovè River. They noted that the name Hotoun attributed to Parachana obscura is due to its snake-like morphology.…”
Section: Traditional Nomenclature Of Local Names Of Fish Speciesmentioning
confidence: 99%
See 1 more Smart Citation